1998
DOI: 10.1021/ic971047x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction and Anticancer Activity of Platinum(IV) Complexes

Abstract: A series of PtIV anticancer complexes with chloro leaving groups have been investigated for the effects of axial and carrier ligands on the reduction and cytotoxicity. The reduction rates of the PtIV complexes such as Pt(d,l)(1,2-(NH2)2C6H10)Cl4 (tetraplatin, Pt(dach)Cl4; dach = diaminocyclohexane), cis,trans,cis-[Pt((CH3)2CHNH2)2(OH)2Cl2] (iproplatin, Pt(ipa)(OH)2Cl2; ipa = isopropylamine), cis,trans,cis-[Pt(NH3)(C6H11NH2)(OCOCH3)2Cl2] (JM-216, Pt(a,cha)(OCOCH3)2Cl2; a = ammine, cha = cyclohexylamine), cis,tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
219
1
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(252 citation statements)
references
References 19 publications
22
219
1
10
Order By: Relevance
“…These values indicate that the presence of the polymeric backbone does not significantly influence the electronic or steric environment of the tethered platinum center and that this construct will effectively release active cisplatin required for anticancer activity. The low values of the cathodic peak for PLA-Pt(IV) also augurs well for the clinical requirement that this construct not be prematurely released in blood (42,43).…”
Section: Resultsmentioning
confidence: 56%
“…These values indicate that the presence of the polymeric backbone does not significantly influence the electronic or steric environment of the tethered platinum center and that this construct will effectively release active cisplatin required for anticancer activity. The low values of the cathodic peak for PLA-Pt(IV) also augurs well for the clinical requirement that this construct not be prematurely released in blood (42,43).…”
Section: Resultsmentioning
confidence: 56%
“…The knowledge of the reactivity of Pt(IV) compounds towards the reduction by potential bioreductant like ascorbic acid may be important for understanding the mechanism of where antitumor activity as well as for designing new compounds with the least side effect. Chois et al [17] reported that there is a correlation between the rate of the reduction and anticancer activity in a series of homologous Pt(IV) complex without going into the details of reaction mechanism. The present study was undertaken with the aim of extending the knowledge of the kinetics and thermodynamic parameters that characterized the reduction of Pt(IV) complex by ascorbic acid and clarifying the mechanism details using the model complex PtCl 6 2− .…”
Section: Introductionmentioning
confidence: 99%
“…The cathodic reduction potential depends on the electronwithdrawing power and the bulkiness of the axial and auxiliary ligands. The low reduction potential of mitaplatin is influenced by the presence of chlorine atoms from the DCA molecules near the platinum center (29).…”
mentioning
confidence: 99%